Structure-based identification of aporphines with selective 5-HT2A receptor-binding activity - Munusamy, V.; Yap, B.K.; Buckle, M.J.C.; Doughty, S.W.; Chung, L.Y. (2013)
Selective blockade of the serotonin 5-HT2A receptor is a useful therapeutic approach for a number of disorders, including schizophrenia, insomnia and ischaemic heart disease. A series of aporphines were docked into a homology model of the rat 5-HT2A receptor using AutoDock. Selected compounds with high in silico binding affinities were screened in vitro using radioligand-binding assays against rat serotonin (5-HT1A and 5-HT2A) and dopamine (D1 and D2) receptors. (R)-Roemerine and (+/-)-nuciferine were found to have high affinity for the 5-HT2A receptor (Ki = 62 and 139 nm, respectively), with (R)-roemerine showing 20- to 400-fold selectivity for the 5-HT2A receptor over the 5-HT1A, D1 and D2 receptors. Investigation into the ligandreceptor interactions suggested that the selectivity of (R)-roemerine is due to it having stronger H-bonding and dipoledipole interactions with several of the key residues in the 5-HT2A receptor-binding site.